Businesses for People with Disabilities in the Digital Age:Protected or Neglected? Revitalizing the Law for an Equal Ecosystem - Farhani, Siti; Ridwan Fachri, Muhammad (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Digital transformation offers significant economic opportunities, yet disabled entrepreneurs in Indonesia still face the risk of marginalization due to the gap between normative legal guarantees and the reality of digital inclusion. This study aims to analyze the legal and non-legal challenges faced by disabled entrepreneurs in the digital ecosystem, evaluate the effectiveness of the national legal framework (particularly Law No. 8 of 2016), and formulate a legal revitalization model to create an equitable digital ecosystem. Using normative legal research methods through statutory, conceptual, and comparative policy analysis approaches, this study concludes that disabled entrepreneurs are more likely to be "neglected" due to systemic barriers, such as the absence of mandatory legal standards for digital accessibility (WCAG), non-accommodative administrative procedures, vulnerability to cybercrime, as well as stigma and limited access to funding. Critical findings indicate that Law No. 8 of 2016 has not been operationalized into adequate technical regulations for the digital space. Therefore, this study recommends legal revitalization through regulatory harmonization, incentives for digital platforms, and a multi-stakeholder collaborative governance model. This revitalization is an absolute prerequisite for transforming the position of disabled entrepreneurs from "neglected" to "protected" in an inclusive and equitable digital ecosystem.